Nghiên cứu tổng hợp, đặc trưng vật liệu mao quản trung bình Al-MSU và xác định hoạt tính xúc tác trong phản ứng crackinh phân tử lớn. Phần II - Đánh giá tính chất xúc tác của vật liêu Al-MSU trong phản ứng cracking phân tử lớn TIPB - Đồng, Đỗ Xuân; Thanh Loan, Nguyễn Thị; Tuấn, Vũ Anh; Tuyến, Nguyễn Đình; Hoài Nam, Lê Thị (Vietnam Journal of Chemistry, 2014)
Al-MSU mesoporous materials were successfully synthesized by hydrothermal treatment using water glass as a Si-sources). Acidity of the sample was measured by NH3-TPD method. The catalytic activity of the samples was tested on the cracking of small and large molecular (n-hexane and tri-isopropylbenzen (TIBP). The results showed that the Al-MSU mesoporous materials were very active for cracking of large molecule (TIBP)